Berichus and the Evidence for Aspar’s Political Power and Aims in the Last Years of Theodosius II’s Reign - Pigoński, Łukasz (Studia Ceranea, 2018)
The article examines Priscus’s account of the conflict that emerged between the leader of the Roman embassy, Maximinus, and the Hunnic envoy, Berichus. The barbarian got offended by the remarks concerning the lack of competence and influence of Aspar and Areobindus. A detailed analysis of this short passage – entailing the persona of Berichus himself, the reasons for his anger, and the possible explanations for Maximinus’s behaviour – can provide us with evidence regarding the political position of Aspar in the last years of the reign of Theodosius II. Most scholars use this example to illustrate Aspar’s falling out of favour and power; it is more likely, however, that the situation was actually more complex. The political struggle between Chrysaphius, a proponent of the policy of reconciliation with the Huns, and Zeno, the opponent of such policies, makes it far more probable that the government feared that their diplomatic effort might be hijacked by the opposing faction. Therefore, it was political differences – and not the failures in the war of 447 – that were the reason for Aspar’s falling out with the emperor. This would also mean that Zeno and Aspar shared similar views on how to solve the Hunnic problem, which would be the basis for their cooperation, resulting in the overthrowing of Chrysaphius and the crowning of Marcian in 450.